THE FORMATION OF FLUIDIZED EJECTA ON MARS BY GRANULAR FLOWS - Wada K.; Barnouin-Jha O.S. (My University, 2006)
A simple granular flow model is used to investigate some of the conditions under which ejecta may flow as a granular media. The purpose of this investigation is to provide some bounds as to when either volatiles or an atmosphere are required to explain the fluid-like morphology of many Martian ejecta deposits. We consider the ejecta deposition process from when an ejecta curtain first strikes a target surface via ballistics and possibly flows thereafter. A new finding is that either hard-smooth surfaces or slightly erodible surfaces allow ejecta to flow readily as a granular medium. Neither volatiles nor an atmosphere are required to initiate flow. A low friction coefficient between ejecta grains can also generate flow and would be analogous to adding volatiles to the ejecta. The presence of either a rough or a densely packed erodible surface does not permit easy ejecta flow. High friction coefficients between ejecta grain also prevent flow, while changes in the coefficient of restitution (a measure of how much energy is retained after collisions between particles) plays a minor role in the flow dynamics of ejecta. A hard smooth or a somewhat erodible surface could be generated by past fluvial activity on Mars, which can either indurate a surface, erode and smooth a surface, or generate sedimentary terrains that are fairly easy to erode. No ramparts or layered ejecta morphologies are generated by our model, but this may be because several simplifying assumptions are used in our model and should not be construed as proof that either volatiles or an atmosphere are required to form fluidized ejecta morphologies. © The Meteoritical Society, 2006.